2021
DOI: 10.2147/ceor.s286283
|View full text |Cite
|
Sign up to set email alerts
|

The Trend of Direct Medical Cost of Meliodiosis Patients in Kedah: A Retrospective Study from 2014 to 2017

Abstract: Purpose This study was conducted to determine the direct medical cost of treating melioidosis patients. The calculation was made according to the variables extracted from medical records. Materials and Methods Data collection was performed retrospectively on a total of 293 cases from Hospital Sultanah Bahiyah, Kedah, Malaysia. The data consisted of personal information, treatment history, and investigation findings, including blood results, USG abdomen results, and CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[ 6 ] Based on 2014 to 2017, a dead patient's direct medical cost in Kedah, Malaysia, was USD 210.42. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Based on 2014 to 2017, a dead patient's direct medical cost in Kedah, Malaysia, was USD 210.42. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate among melioidosis patients ranges from 14% to 40%, among which >80% of the cases are untreated patients [6] . Based on 2014 to 2017, a dead patient's direct medical cost in Kedah, Malaysia, was USD 210.42 [7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Vietnam reported the cost to detect the selective culture in melioidosis was approximately $100 in Vientiane and $39 in Siem Reap per patient [46]. One reported study on the direct medical cost of melioidosis in Malaysia showed that the cost of treating melioidosis patients increased after the length of hospital stay [47].…”
Section: Economic Burden Of Melioidosismentioning
confidence: 99%